Effects of Low-Level Er:YAG Laser Irradiation on Proliferation and Calcification of Primary Osteoblast-Like Cells Isolated From Rat Calvaria - Niimi, Hiromi; Ohsugi, Yujin; Katagiri, Sayaka; Watanabe, Kazuki; Hatasa, Masahiro; Shimohira, Tsuyoshi; Tsuchiya, Yosuke; Maekawa, Shogo; Hirota, Tomomitsu; Kadokura, Hiroshi; Yokose, Satoshi; Iwata, Takanori; et al. (Frontiers in Cell and Developmental Biology, 2020)
Several reports have shown that the photo-bio-modulation of cells by various lasers has favorable biological effects. However, the effects of low-level Er:YAG laser irradiation on osteoblasts remain unclear. The purpose of this study was to evaluate the effects of low-level Er:YAG laser irradiation on proliferation and osteogenic differentiation of primary osteoblast-like cells isolated from the calvariae of 3–5-day-old Wistar rats. Cells were irradiated by Er:YAG laser at energy fluences of 2.2, 3.3, and 4.3 J/cm2, respectively. After irradiation, cell surface temperatures were measured and cell proliferation was evaluated by flow cytometry and CCK-8. Calcification was evaluated by measuring areas of Alizarin red S staining after 7, 14, and 21 days culture in osteoinductive medium. Gene expression in non-irradiated and laser-irradiated cells was evaluated by qPCR at 3, 6, and 12 hours, as well as 1, 3, 7, and 14 days after irradiation. Microarray analysis was performed to comprehensively evaluate the gene expression of non-irradiated and irradiated cells at 3.3 J/cm2 at 6 hours after irradiation. No pronounced increase of cell surface temperature was induced by irradiation. Irradiation did not affect osteoblast-like cell proliferation. Osteoblast-like cell calcification was significantly increased 7 days after Er:YAG laser irradiation at 3.3 J/cm2. Bglap expression was significantly increased in cells irradiated at 3.3 J/cm2 6 hours post-irradiation. Microarray analysis showed that irradiation at 3.3 J/cm2 caused an upregulation of inflammation-related genes and downregulation of Wisp2. Gene set enrichment analysis also clarified enrichment of inflammation-related and Notch signaling gene sets. In conclusion, low-level Er:YAG laser irradiation at 3.3 J/cm2 enhanced calcification of primary osteoblast-like cells via enhanced Bglap expression and enriched Notch signaling.